The The Analysis of Effectiveness on MSME Financing at Sharia Bankaltimtara Samarinda - Rinna Ramadhan Ain Fitriah; Muh Shadiqul Fajri AF (Eastasouth Institute, 2022)
The MSME sector has a significant role in improving the national economy, including employment, increasing people's income, and alleviating poverty. Until now, the main problem faced by MSMEs is capital. This study aims to analyze the effectiveness of financing the MSME sector at Sharia Bankaltimtara, Samarinda Branch. The method used is by using a survey method, namely the assessment of customer perceptions based on the procedure for submitting a financing application, the financing mechanism and the impact of the provision of financing on the customer's business development. The effectiveness of financing is measured through quantitative analysis and tested with descriptive statistics. This test informs the customer's assessment score and the average value of customer perceptions of the questions studied using a Likert scale. The population in this study is MSME business actors who receive financing from Sharia Bankaltimtara, Samarinda Branch, while the sample in this study was determined using a purposive sampling technique totaling 30 (thirty) respondents. The research instrument uses a questionnaire or a questionnaire distributed to MSME financing customers. Test the validity and reliability of the instrument using SPSS statistics. The results of the analysis show that the MSME financing of Sharia Bankaltimtara Samarinda Branch has been running effectively, customers assess the MSME sector financing has been carried out very effectively based on the ease of the procedure for submitting a financing application.